Survey of ICT and Education in Africa : Sudan Country Report - Hamdy, Amr (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev) - supported survey of the Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. Sudan's experience of the last two decades in building and capitalizing on ICT as a gateway for sustainable development is a landmark in the country's history. The institutional, legal, and regulatory frameworks were reformed to advance ICT as tools for integrating the economy into the global market. The Sudanese government has budgeted future revenues for infrastructure refurbishments, and a multi-donor trust fund (MDTF) - administered by the World Bank was created to support development projects. Investments from the MDTF will be divided between the Government of Southern Sudan (GOSS) and the national government in Khartoum. In November 2005, the MDTF gave the first disbursement of $20 million to the GOSS for the rebuilding of health and education services. However, the full potential of ICT is greatly hampered by the lack of capacity of communities to make the best use of the services. Therefore, United Nations Development Program (UNDP) is intervening to assist the government through its ICT institutions to promote ICT for human development.